If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6d + 18 = 0 Reorder the terms: 18 + 6d = 0 Solving 18 + 6d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6d = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6d = 0 + -18 6d = 0 + -18 Combine like terms: 0 + -18 = -18 6d = -18 Divide each side by '6'. d = -3 Simplifying d = -3
| 9+ln(8x)=21-2ln(x) | | 7-15=5x | | 30t^2=22t | | (6+x)(5x-6)= | | -7(5m)= | | 25t^2=25 | | 7.5*6.3=x | | -3x-8=46 | | p(x)=x^2-25 | | 3x+69=8x-6 | | 12(4X-3)=4(12X+5) | | 9x-2x^2=3x^2-2 | | 15x-14=61 | | -7(5m)=-35m | | 12y-4y=32 | | (7x^2-12x+2)=0 | | 259-5x=40x+24 | | 2x+2=11x+9 | | (13/52)*(13/52) | | -(7x^2-12x+2)=0 | | 2(2x-7)(4x+3)=0 | | (6x-4)^1-4=(5+3x)^1/4 | | 11x-14=30 | | 4x-5/7=2z | | (-6a+8b-c)-(-2b+4c-6d)= | | 6+4(1+2m)=3(m+3)+1 | | -3x-12=9 | | -14x^2+12x-2=0 | | x^3=x^2-7 | | -14x+12x-2=0 | | 10(12+y)/2=100 | | 3x-17=2y |